2018
DOI: 10.1371/journal.pgen.1007315
|View full text |Cite
|
Sign up to set email alerts
|

The presence of rNTPs decreases the speed of mitochondrial DNA replication

Abstract: Ribonucleotides (rNMPs) are frequently incorporated during replication or repair by DNA polymerases and failure to remove them leads to instability of nuclear DNA (nDNA). Conversely, rNMPs appear to be relatively well-tolerated in mitochondrial DNA (mtDNA), although the mechanisms behind the tolerance remain unclear. We here show that the human mitochondrial DNA polymerase gamma (Pol γ) bypasses single rNMPs with an unprecedentedly high fidelity and efficiency. In addition, Pol γ exhibits a strikingly low freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 56 publications
(88 reference statements)
1
45
0
Order By: Relevance
“…The persistent rNMPs found in mtDNA are therefore not due to unusually poor discrimination against rNTPs by the mtDNA polymerase. As has been found for many other DNA polymerases, the exonuclease activity of Pol ɣ does not contribute to rNMP removal .…”
Section: Ribonucleotides Are Incorporated During Mtdna Replication Ansupporting
confidence: 65%
See 4 more Smart Citations
“…The persistent rNMPs found in mtDNA are therefore not due to unusually poor discrimination against rNTPs by the mtDNA polymerase. As has been found for many other DNA polymerases, the exonuclease activity of Pol ɣ does not contribute to rNMP removal .…”
Section: Ribonucleotides Are Incorporated During Mtdna Replication Ansupporting
confidence: 65%
“…The rNMPs found in mature mtDNA are therefore not related to the lengthy RNA species that temporarily coat the displaced H-strand in the RITOLS model nor are they longer RNA primers left unremoved after replication initiation. The estimated number of rNMPs per double-stranded mtDNA molecule ranges from 36 and 54 rNMPs in cultured HeLa and primary fibroblast cell lines, respectively [9], to 65 rNMPs in mouse liver [8]. In accordance with these numbers, Moss et al [65] reported a higher frequency of rNMPs in solid tissues than in cultured cell lines.…”
Section: Features Of Mtdna and Its Replicationmentioning
confidence: 87%
See 3 more Smart Citations